Bone morphogenetic proteins (BMPs) and their role in poultry. Issue 3 (3rd July 2021) - Divya, D.; Bhattacharya, T. K.
SUMMARY: The chicken is considered to be a major inexpensive protein producer of animal origin across the world. Enormous progress has been attained to improve production and reproduction by intense genetic selection, but it has resulted in indirect introduction of unwanted characteristics such as a strain on the birds' skeletal system. Several genetic and non-genetic factors affect bone growth and integrity. Bone morphogenetic proteins (BMPs) belong to the transforming growth factor-beta (TGFβ) superfamily and comprise one of the multifunctional growth factors involved in organogenesis. Briefly, BMPs are known to play varied roles in embryogenesis, limb morphogenesis, cardiac myofibrillogenesis, odontogenesis, folliculogenesis, tissue-homoeostasis and left-right chick patterning. Yet, few BMPs have been detected and assessed in the chicken and were found to be located differently on the chromosomes from mammals. BMP's 1-like, 2, 3, 4, 5, 6 and 7 and BMP's specific receptors (BMPR1A, BMPR1B and BMPR2) are expressed in osteoblasts and chondrocytes implicating their important role in osteo-chondrogenesis in chickens. However, some of the BMPs such as BMP2, 4, 5, 6, 7 and 15 were also, surprisingly, detected in ovaries (granulosa and theca cells) and BMP2, 4 and 7 and BMPR1A, BMPR1B and BMPR2 in retinal pigment epithelium indicating their function in ovarian follicles and eye development in chicks. A number of antagonists have been identified as having a role in the signalling cascade of the bone morphogenetic proteins pathway. This review discusses the BMPs so far identified in chickens and their signalling and functioning for further use in improving skeletal strength and health of chickens.